Prevalence, Etiology, and Risk Factors of Tinea Pedis and Tinea Unguium in Tunisia - Nourchène Toukabri; Cyrine Dhieb; Dalenda El Euch; Mustapha Rouissi; Mourad Mokni; Najla Sadfi-Zouaoui (Canadian Journal of Infectious Diseases and Medical Microbiology)
Background. Foot mycoses are a frequent disease that represents a public health problem worldwide. Objectives. This study aims to evaluate the epidemiology of foot mycoses among Tunisian patients, in order to determine the fungal etiological agents and to identify possible risk factors. Patients and Methods. A prospective study of three hundred and ninety-two patients was undertaken during one year (2013-2014). All subjects were asked to collect demographic data related to the risk factors of foot mycoses. A complete mycological diagnosis was carried out on all patients. Results. A total of 485 samples were collected; tinea pedis and tinea unguium were confirmed in 88.2% of cases. Dermatophytes were isolated in 70.5% and the most frequent pathogen was Trichophyton rubrum (98.1%), followed by yeasts (17.7%) commonly Candida parapsilosis. Non-dermatophyte molds (NDMs) were observed in 8.02% cases and Fusarium sp. was the frequent genus (29.1%). The main predisposing factors of fungal foot infections were practicing ritual washing (56.6%) and frequentation of communal showers (50.5%). Conclusion. This is a recent survey of foot mycoses in Tunisia. Epidemiological studies can be useful to eradicate these infections and to provide further measures of hygiene and education.